Korelasi Nyeri Dada dan Aktivitas Fisik pada Pasien Jantung Koroner:Studi di RSUD H. Boejasin Kabupaten Tanah Laut - Solikin, Solikin; Maysita, Zea; Nurhikmah, Nurhikmah (STIKES Suaka Insan, 2025)
Chest pain is a primary symptom in patients with coronary heart disease (CHD), often limiting physical activity and reducing quality of life. This study aimed to identify the relationship between chest pain intensity and physical activity among CHD patients at H. Boejasin District Hospital, Tanah Laut. A quantitative correlational design was employed, involving 94 patients selected by purposive sampling. Chest pain was measured using the Numeric Rating Scale (NRS), and physical activity was assessed with the Global Physical Activity Questionnaire (GPAQ) from WHO. The results showed that most respondents experienced moderate chest pain (78.7%) and engaged in light physical activity (74.5%). Spearman's rho test revealed a significant correlation between chest pain and physical activity (correlation coefficient 0.649; p < 0.05), indicating that higher levels of chest pain are associated with lower levels of physical activity. These findings highlight the importance of optimal pain management in CHD patients to support increased physical activity and prevent further complications. The use of standardized instruments such as NRS and GPAQ is crucial in nursing practice to monitor patients’ conditions comprehensively.